Overview of Knowledge of Couples of Childbearing Age Signs of Pregnancy in Nagori, Bandar Malaka District, Gunung Maligas District, Simalungun Regency - Santi Widya Purba; Sri Rahma Friani; Dini Pajriani Khairunnisa (Sean Institute, 2025)
Not all couples of childbearing age (PUS), have healthy reproduction in the sense of having fertility that is ready to be fertilized or fertilized. To overcome this, most PUS choose to have children through artificial conception. Based on the rules that apply in Indonesia, namely Law No. 32 of 1992 concerning Health article 16 paragraphs 1 and 2 and Law No. 39 of 1999 concerning Human Rights article 10 paragraph 1, only artificial conception through a legal marriage is allowed. So that artificial conceptions through sperm donors of other people who are not legally married are unlawful acts and contrary to the human rights that apply in Indonesia.From the results of the study with the title